2015
DOI: 10.1111/bph.13268
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity to intravenous iron: classification, terminology, mechanisms and management

Abstract: Intravenous (IV) iron therapy is widely used in iron deficiency anaemias when oral iron is not tolerated or ineffective. Administration of IV-iron is considered a safe procedure, but severe hypersensitivity reactions (HSRs) can occur at a very low frequency. Recently, new guidelines have been published by the European Medicines Agency with the intention of making IV-iron therapy safer; however, the current protocols are still non-specific, non-evidence-based empirical measures which neglect the fact that the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
137
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(141 citation statements)
references
References 75 publications
2
137
0
2
Order By: Relevance
“…[6,10,11] However, several authors have suggested that these antihistamines should not be administered because they could cause adverse effects that could be misinterpreted as DHRs, such as a slight urticariform reaction [12][13][14][15]. Moreover, some authors suggest that corticosteroids have a greater influence on anaphylaxis than on DHRs; therefore, their usefulness in the initial part of the protocol should be reassessed [12]. Other authors have suggested that premedication should be omitted completely, although such modifications to the protocol are still being investigated [7].…”
Section: Discussionmentioning
confidence: 99%
“…[6,10,11] However, several authors have suggested that these antihistamines should not be administered because they could cause adverse effects that could be misinterpreted as DHRs, such as a slight urticariform reaction [12][13][14][15]. Moreover, some authors suggest that corticosteroids have a greater influence on anaphylaxis than on DHRs; therefore, their usefulness in the initial part of the protocol should be reassessed [12]. Other authors have suggested that premedication should be omitted completely, although such modifications to the protocol are still being investigated [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, this is now off the market and has been replaced by new iron preparations such as low-molecular-weight iron dextran, ferum­oxytol, ferric carboxymaltose, and iron isomaltoside. Studies have shown all iron products have a good safety record, with a lower rate of reactions than rituximab or penicillin [28]. Modern iron formulations are associated with a low risk of reactions, and they have fewer adverse effects than oral iron in several studies.…”
Section: Risks Of Intravenous Ironmentioning
confidence: 99%
“…More serious "anaphylactoid" reactions, including hemodynamic and respiratory changes, can also occur with virtually all IV iron preparations, including the newer ones (see below), but appear exceedingly rare (see below). At variance with serious AEs with old compound like iron-HMWD, for whom in some cases a IgE-mediated mechanisms could be demonstrated [104,105], such reactions are now increasingly attributed to complement activation-related pseudo-allergy (CARPA) [106]. This mechanism is thought to be activated by iron nanoparticles [106], thus, again, the stability of the carbohydrate shell and the different physicochemical properties of the various compounds are likely critical.…”
Section: The Chemistry Of Different IV Iron Preparations and Its Relamentioning
confidence: 99%
“…At variance with serious AEs with old compound like iron-HMWD, for whom in some cases a IgE-mediated mechanisms could be demonstrated [104,105], such reactions are now increasingly attributed to complement activation-related pseudo-allergy (CARPA) [106]. This mechanism is thought to be activated by iron nanoparticles [106], thus, again, the stability of the carbohydrate shell and the different physicochemical properties of the various compounds are likely critical. Anyway, a recent systematic meta-analysis of 103 trials including more than 10,000 patients treated with various IV iron preparations and more than 7000 patients treated with different comparators (oral iron, placebo) found serious AEs with IV iron extremely rare (< 1,200,000 doses), and no more frequent than comparators [107].…”
Section: The Chemistry Of Different IV Iron Preparations and Its Relamentioning
confidence: 99%